(untitled) (Journal of the College of Basic Education, 2023)
This study was aimed to estimeated at chemical composition and evaluating the effectivenes of the extract of Artemisia monosperma and Salvia officinalis L. against four species of illness bacteria that causing and food spoileg. The result were refer to found a number of effective compounds in plant extract like Glycosides , Flavonoids , Resins, Alkaloids, Phenols and Trace elements (Co, Zn, Fe, Pb, Cd and Cu). The results of Microbiological tests were showed some difference between the effect of this plants on the declining of the bacterical species growth. Inhibition zone against bacteria was (11-23.5)mm and the (MIC) were 10 - 30 mg/ml for alcoholic extracts against becterial species tested.